2021
DOI: 10.1530/eje-21-0024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hormonal findings in patients presenting with high IGF-1 and growth hormone suppression after oral glucose load: a retrospective cohort study

Abstract: Objective: high IGF-1 and unsuppressed GH levels after glucose load confirm the diagnosis of acromegaly. Management of patients with conflicting results could be challenging. Our aim was to evaluate the clinical and hormonal evolution over a long follow-up in patients with high IGF-1 but normal GH nadir (GHn<0.4 μg/L according to the latest guidelines). Design: retrospective cohort study. Methods: we enrolled 53 patients presenting high IGF-1 and GHn<0.4 μg/L, assessed because of clinical suspicion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Although our results differ from some studies that used higher normal bGH cutoff levels (Dimaraki et al 2002;Ribeiro-Oliveira et al 2011;Butz et al 2016;Gomes et al 2019), they coincide with the results of Machado et al (2008) and Espinosa de los Monteros et al (2018) (5.9% and 3%, respectively) (Table 3). It is important to note that few studies have defined micromegaly as high IGF-I level and nadir postglucose GH <0.4 ng/mL (Subbarayan et al 2012;Carosi et al 2021). Carosi et al (2021) have described twenty-five patients with acromegalic features with high IGF-I and nadir post-glucose GH <0.4 ng/mL ("micromegalic group"), comparing them with twenty-eight patients with high IGF-I levels and nadir post-glucose GH <0.4 ng/mL despite no clear clinical suspicion of acromegaly (Carosi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our results differ from some studies that used higher normal bGH cutoff levels (Dimaraki et al 2002;Ribeiro-Oliveira et al 2011;Butz et al 2016;Gomes et al 2019), they coincide with the results of Machado et al (2008) and Espinosa de los Monteros et al (2018) (5.9% and 3%, respectively) (Table 3). It is important to note that few studies have defined micromegaly as high IGF-I level and nadir postglucose GH <0.4 ng/mL (Subbarayan et al 2012;Carosi et al 2021). Carosi et al (2021) have described twenty-five patients with acromegalic features with high IGF-I and nadir post-glucose GH <0.4 ng/mL ("micromegalic group"), comparing them with twenty-eight patients with high IGF-I levels and nadir post-glucose GH <0.4 ng/mL despite no clear clinical suspicion of acromegaly (Carosi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that few studies have defined micromegaly as high IGF-I level and nadir postglucose GH <0.4 ng/mL (Subbarayan et al 2012;Carosi et al 2021). Carosi et al (2021) have described twenty-five patients with acromegalic features with high IGF-I and nadir post-glucose GH <0.4 ng/mL ("micromegalic group"), comparing them with twenty-eight patients with high IGF-I levels and nadir post-glucose GH <0.4 ng/mL despite no clear clinical suspicion of acromegaly (Carosi et al 2021). Interestingly, they found that the coexistence of acromegalic features and a nadir post-glucose GH ≥0.1 ng/mL were strongly associated with the presence of a high rate of acromegalic comorbidities (sensitivity=50%; specificity=86%) (Carosi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 At present, the widely accepted diagnostic workup for acromegaly includes a screening IGF-1 and, if elevated, an oral glucose tolerance test (OGTT) with GH nadir of >1 μg/L or >0.4 μg/L depending on assay methodology. 6,7 The 2014 Endocrine Society Guidelines suggest using a GH cut off <1 μg/L is sufficient to exclude the diagnosis. 2 There are published series however, of patients with clinical features and histological evidence of acromegaly with elevated IGF-1 but adequate GH suppression during OGTT before treatment, leading to the term 'micromegaly'.…”
mentioning
confidence: 99%
“…8 Case-based observations and previous studies suggest that elevated IGF-1 occurs in patients without clinical acromegaly. 7 Elevated IGF-1 in those without acromegaly has the potential to create unnecessary anxiety for patients, diagnostic uncertainty in clinical practice and can lead to financial costs for additional investigations. A retrospective case-control study was conducted to identify the frequency of IGF-1 elevation in a cohort of patients without clinically suspected GH excess in a single state-based reference laboratory (Pathology Queensland) over a 24-month period using the Diasorin Liaison XL chemiluminescence immunoassay.…”
mentioning
confidence: 99%